“COMPARATIVE EVALUATION OF FRACTURE STRENGTH, SURFACE HARDNESSAND COLOR STABILITY BETWEEEN PRE-FORMED AND CUSTOMIZABLE DIRECT VENEERS: AN IN-VITRO STUDY” (Journal of Pharmaceutical Negative Results, 2022)
Background: Dental veneers are steadily increasing in popularity among today’s dental practitioners for rehabilitation of unaesthetic anterior teeth. The art of veneering has progressed over many years to the current generation of concepts and materials, which can be divided into directly fabricated composite resin veneers and indirectly fabricated veneers e.g., preformed laminates or laboratory fabricated acrylic resin, micro filled resin / indirect composite or porcelain veneers. The aim of the present study was to compare and evaluate the fracture strength, surface hardness and color stability between pre-formed and customizable direct veneers.Materials and Method: The materials evaluated as study groups were composed of two groups namely, preformed veneers and discs (Edelweiss, Austria) (N=30) and Direct composite veneers and discs (Tetric N Ceram, Ivoclar Vivadent) (N=30). Both the groups were subdivided into two sub groups, each subgroup consisted of 15 veneers and 15 discs. 30 extracted human maxillary central incisors were selected and intra enamel veneer preparation was done and divided into two groups of (N=15) as stated above. 15 preformed discs (Edelweiss, Austria) were used and 15 direct composite discs (Tetric N Ceram) were prepared using a Teflon mould (8mm × 2mm), finished and polished. The fracture strength was performed by Universal Testing Machine at a cross head speed of 1 mm/min on the preformed veneers. Surface hardness was measured on the disc samples by a digital micro hardness tester. The finished samples were stored dry at room temperature 7 days prior to testing. The Vickers Hardness Test was used to measure the hardness. Color stability was measured for the disc samples at baseline (standard) and final (after immersion for 30 days) by a spectrophotometer. Tea and coffee were used as the immersing solutions. Color values (L*, a*, b*) were measured over a white background, using CIE L*a*b* system. The data were statistically analyzed with independent ‘t’ test.Result: The mean score value of fracture strength, surface hardness and color stability were seen to be more for pre- formed veneers as compared to the direct composite veneers. The difference between them was deemed to be very highly statistically significant (p<0.001) (Independent ‘t’ test).Conclusion: The preformed veneers seem to have better mechanical properties as compared to direct composite veneers.